"She was all brittle crystal": The "Girl" and Anthony Burgess's The Brides of Enderby. Issue 1 (2nd January 2017) - Rowley, Carly Eloise
ABSTRACT: The song cycle The Brides of Enderby (1977), composed by author and critic Anthony Burgess (1917–1993), has a complex, multi-layered authorship. Although Burgess originally wrote the cycle's poetry in his youth, he attributed these texts to his fictional protagonist, Francis Xavier Enderby (from the Enderby series of novels). The text of the fifth movement, "She was all brittle crystal, " is his early poem "Girl" (c. 1939), which is thought to concern Burgess's first wife, Llewela (Lynne). The movement serves as a means to explore how Burgess's musical response here articulates a Muse figure, both aloof and intransient. The song cycle demonstrates Burgess's lifelong interest in the connections between music and literature, and offers the opportunity to examine both the relationship between Burgess and Enderby, and the musical decisions Burgess made in setting a text that he attributed to his alter ego.